(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Our aim was To determine if there is baseline elevation of troponin T and creatine kinase-MB in native congenital heart disease and to evaluate the accuracy of these biomarkers for prediction of myocardial injury in congenital heart disease. Methods: This study included 70 age and sex-matched children. All of them underwent Echocardiographic and tissue Doppler examinations and estimation of serum creatine kinase-MB and cardiac troponinT. Results: Creatine kinase-MB and cardiac troponinT were higher in cases compared with controls [2.48 (0.43 - 27.82) and 17.5 (4.12 - 186.2) vs 1.97 (0.9 - 4.1) and 7.5 (3 - 13.8) ng/ml, p values 0.003]. Mitral E`/A` velocity ratio was less in patients than controls (1.75± 0.48 vs 2.18± 0.57 cm/sec, p=0.002). Accuracy of creatine kinase-MB and cardiac troponinT in prediction of myocardial injury in native congenital heart disease were67.1% and 87.1% respectively. Conclusion:Subtle myocardial injury and subclinical LV diastolic dysfunction are present in our patients. Serum cardiac troponinT is a more sensitive and specific marker of myocardial injury compared with creatine kinase-MB.